Exposure of the lungs in breast cancer radiotherapy: A systematic review of lung doses published 2010–2015. Issue 1 (January 2018) - Aznar, Marianne C.; Duane, Frances K.; Darby, Sarah C.; Wang, Zhe; Taylor, Carolyn W.
Abstract: Background and purpose: We report a systematic review of lung radiation doses from breast cancer radiotherapy. Methods and materials: Studies describing breast cancer radiotherapy regimens published during 2010–2015 and reporting lung dose were included. Doses were compared between different countries, anatomical regions irradiated, techniques and use of breathing adaptation. Results: 471 regimens from 32 countries were identified. The average mean ipsilateral lung dose (MLDipsi ) was 9.0 Gy. MLDipsi for supine radiotherapy with no breathing adaption was 8.4 Gy for whole breast/chest wall (WB/CW) radiotherapy, 11.2 Gy when the axilla/supraclavicular fossa was irradiated, and 14.0 Gy with the addition of internal mammary chain irradiation; breathing adaptation reduced MLDipsi by 1 Gy, 2 Gy and 3 Gy respectively ( p  < 0.005). For WB/CW radiotherapy, MLDipsi was lowest for tangents in prone (1.2 Gy) or lateral decubitus (0.8 Gy) positions. The highest MLDipsi was for IMRT in supine position (9.4 Gy). The average mean contralateral lung dose (MLDcont ) for WB/CW radiotherapy was higher for IMRT (3.0 Gy) than for tangents (0.8 Gy). Conclusions: Lung doses from breast cancer radiotherapy varied substantially worldwide, even between studies describing similar regimens. Lymph node inclusion and IMRT use increased exposure, while breathing adaptation and prone/lateral decubitus positioning reduced it.